Pengaruh Keputusan Investasi Dan Makro Ekonomi Melalui Operasional Terhadap Nilai Perusahaan - Lu’lu’il Maknuun (Jurnal Dinamika Ekonomi Syariah, 2020)
This study aims to determine and analyze the effect of investment decisions and macroeconomics through operations to firm value. This study uses a quantitative approach. the data analysis method used in this study is the Smart Partial Least Square (PLS) software. The effect of investment decisions on operations, the relationship between the two variables is a significant negative. The effect of investment decisions with firm value, the relationship between the two variables is significantly positive. The influence of macroeconomics on operations, the relationship between the two is negative is not significant. The influence of macroeconomic with firm value, the relationship between two variables is not significant positive. The operational effect on firm value, the relationship between the two variables is significantly positive.